Evaluation of Xpert MTB/RIF for Detection of Mycobacterium tuberculosis in Cerebrospinal Fluid - Pink, F.; Brown, T. J.; Kranzer, K.; Drobniewski, F. (Journal of clinical microbiology, 2016)
Studies investigating Xpert MTB/RIF diagnostic performance on cerebrospinal fluid (CSF) samples are lacking in resource-rich settings. Xpert MTB/RIF results for 740 CSF samples from 698 patients across England were retrospectively compared with the results of culture of the same and contemporary samples. The overall sensitivity was calculated at 55%.